2015
DOI: 10.1136/annrheumdis-2015-eular.6727
|View full text |Cite
|
Sign up to set email alerts
|

SP0191 Measuring Quality of Life in Young Adults with Jia in Clinical Practice

Abstract: BackgroundChildren and adolescents with Juvenile Idiopathic Arthritis (JIA) are at risk for the development of psychosocial problems and a lowered Health Related Quality of Life (HRQOL). These problems are not always identified during consultations with a rheumatologist. Therefore, adequate screening, monitoring and providing tailored interventions is necessary. The goal of the KLIK program is therefore to monitor the HRQOL and psychosocial functioning of children and young adults with chronic illnesses over e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Of the 23 clinical, non-medical switching studies (Table 1) [53, 55, 56, 60, 61, 69, 70, 7375, 81, 82, 8486, 91–99, 101104], 22 reported data on main efficacy parameters in switched versus non-switched or pre-switch versus post-switch groups. The originator biologics/biosimilars assessed were infliximab (six studies [53, 55, 56, 61, 69, 70, 73]), erythropoietin-stimulating agents (ESAs) (four studies [74, 75, 81, 82]), filgrastim [9395] (three studies), insulin [8486], adalimumab [96–98], rituximab [60, 99] and etanercept [101103] (two studies each), and genotropin [83, 92] and follicle stimulating hormone [104] (one study each).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 23 clinical, non-medical switching studies (Table 1) [53, 55, 56, 60, 61, 69, 70, 7375, 81, 82, 8486, 91–99, 101104], 22 reported data on main efficacy parameters in switched versus non-switched or pre-switch versus post-switch groups. The originator biologics/biosimilars assessed were infliximab (six studies [53, 55, 56, 61, 69, 70, 73]), erythropoietin-stimulating agents (ESAs) (four studies [74, 75, 81, 82]), filgrastim [9395] (three studies), insulin [8486], adalimumab [96–98], rituximab [60, 99] and etanercept [101103] (two studies each), and genotropin [83, 92] and follicle stimulating hormone [104] (one study each).…”
Section: Resultsmentioning
confidence: 99%
“…The originator biologics/biosimilars assessed were infliximab (six studies [53, 55, 56, 61, 69, 70, 73]), erythropoietin-stimulating agents (ESAs) (four studies [74, 75, 81, 82]), filgrastim [9395] (three studies), insulin [8486], adalimumab [96–98], rituximab [60, 99] and etanercept [101103] (two studies each), and genotropin [83, 92] and follicle stimulating hormone [104] (one study each).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations